The Role of Eastern and National Values in Educating a Healthy Faith (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article presents information about the education of the young generation with high spirituality and healthy beliefs, and it is also important to instill in the minds of students such values as human qualities, kindness and honor, and in this regard it is stated that the great should use the humanitarian essence of Islamic philosophy. As a socio-pedagogical factor, hadiths are a means of effective influence on the formation of the mature generation, and its incomparable importance in the education of healthy faith is analyzed from a practical point of view. It is explained that values should be perceived on the basis of a new way of thinking and deeply observed.